Enhanced In Vivo Vascularization of 3D‐Printed Cell Encapsulation Device Using Platelet‐Rich Plasma and Mesenchymal Stem Cells. Issue 19 (31st August 2020) - Paez‐Mayorga, Jesus; Capuani, Simone; Farina, Marco; Lotito, Maria Luisa; Niles, Jean A.; Salazar, Hector F.; Rhudy, Jessica; Esnaola, Lucas; Chua, Corrine Ying Xuan; Taraballi, Francesca; Corradetti, Bruna; Shelton, Kathryn A.; et al.
Abstract: The current standard for cell encapsulation platforms is enveloping cells in semipermeable membranes that physically isolate transplanted cells from the host while allowing for oxygen and nutrient diffusion. However, long‐term viability and function of encapsulated cells are compromised by insufficient oxygen and nutrient supply to the graft. To address this need, a strategy to achieve enhanced vascularization of a 3D‐printed, polymeric cell encapsulation platform using platelet‐rich plasma (PRP) and mesenchymal stem cells (MSCs) is investigated. The study is conducted in rats and, for clinical translation relevance, in nonhuman primates (NHP). Devices filled with PRP, MSCs, or vehicle hydrogel are subcutaneously implanted in rats and NHP and the amount and maturity of penetrating blood vessels assessed via histopathological analysis. In rats, MSCs drive the strongest angiogenic response at early time points, with the highest vessel density and endothelial nitric oxide synthase (eNOS) expression. In NHP, PRP and MSCs result in similar vessel densities but incorporation of PRP ensues higher levels of eNOS expression. Overall, enrichment with PRP and MSCs yields extensive, mature vascularization of subcutaneous cell encapsulation devices. It is postulated that the individual properties of PRP and MSCs can be leveraged in a synergistic approach for maximal vascularization of cell encapsulation platforms. Abstract : Vascularization of a subcutaneously implanted cell encapsulation platform is enhanced via enrichment with mesenchymal stem cells (MSCs) or platelet‐rich plasma (PRP) in rats and nonhuman primates. Enrichment with PRP and MSCs increases blood vessel number and maturity inside the encapsulation devices and unveils an optimal window for cell transplantation.